The Influence of Social Support on Employees' Well-being - Andreea Teodora Al-Floarei; Simona Dumitriu; Daniela Victoria Popescu (Ovidius University Annals: Economic Sciences Series, 2025)
The importance of social support in the workplace has been receiving more attention, particularly given its positive impact on employees’ health, workers’ well-being, and job satisfaction. This article explores how support from colleagues and managers influences these critical outcomes. The study uses an artificial neural network model, specifically the multilayer perceptron, to examine the connections between social support and employee health, well-being, and satisfaction. Findings show a strong, positive relationship between social support and physical and mental well-being, underscoring the pivotal role of supportive workplace relationships in boosting employee satisfaction and overall well-being. These results highlight the importance of creating a supportive and inclusive workplace to improve employee outcomes.